NAADP links histamine H1 receptors to secretion of von Willebrand factor in human endothelial cells. - Esposito, B; Gambara, G; Lewis, A; Palombi, F; D'Alessio, A; Taylor, L; Genazzani, A; Ziparo, E; Galione, A; Churchill, G; Filippini, A (2011)
A variety of endothelial agonist-induced responses are mediated by rises in intracellular Ca(2+), suggesting that different Ca(2+) signatures could fine-tune specific inflammatory and thrombotic activities. In search of new intracellular mechanisms modulating endothelial effector functions, we identified nicotinic acid adenine dinucleotide phosphate (NAADP) as a crucial second messenger in histamine-induced Ca(2+) release via H1 receptors (H1R). NAADP is a potent intracellular messenger mobilizing Ca(2+) from lysosome-like acidic compartments, functionally coupled to the endoplasmic reticulum. Using the human EA.hy926 endothelial cell line and primary human umbilical vein endothelial cells, we show that selective H1R activation increases intracellular NAADP levels and that H1R-induced calcium release involves both acidic organelles and the endoplasmic reticulum. To assess that NAADP links H1R to Ca(2+)-signaling we used both microinjection of self-inactivating concentrations of NAADP and the specific NAADP receptor antagonist, Ned-19, both of which completely abolished H1R-induced but not thrombin-induced Ca(2+) mobilization. Interestingly, H1R-mediated von Willebrand factor (VWF) secretion was completely inhibited by treatment with Ned-19 and by siRNA knockdown of 2-pore channel NAADP receptors, whereas thrombin-induced VWF secretion failed to be affected. These findings demonstrate a novel and specific Ca(2+)-signaling mechanism activated through H1R in human endothelial cells, which reveals an obligatory role of NAADP in the control of VWF secretion.